Influence of Accounting Software Quality Dimensions on Intentions to Use of SME’s in South Tangerang - Solihin Solihin; Tugiantoro Tugiantoro (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to obtain empirical evidence regarding the dimensions of quality accounting software which include performance, reliability, features, conformance, and serviceability towards the intention to use accounting software for employees working in micro, small and medium scale companies (SMEs) in the South Tangerang area. This study uses quantitative methods through primary data. Questionnaire data were processed of 87 respondents from 135 questionnaires distributed to employees who work at SME’s companies, the questionnaire used a Likert scale of 1-5. The results study prove that performance, features and serviceability have a significant effect on intentions to use accounting software, while reliability and conformance have no significant effect on intentions to use accounting software.